Rare presentation of ureteral duplication: stone localization in the upper moiety - Chatterjee, Sunayana; Deshmukh, Hrishikesh; Thorat, Vaibhav (International Journal of Research in Medical Sciences, 2023)
This case report describes a rare exception to the typical presentation of complete ureteral duplication, a relatively uncommon condition in comparison to single ureter or partial duplication. The patient presented with right flank pain and imaging revealed a duplex collecting system with a stone located in the upper moiety. Upper moiety complications, such as ectopic ureteric insertion and multicystic dysplastic moiety, are usually observed in duplex kidneys. Contrast-enhanced imaging and endoscopic treatment were utilized for accurate diagnosis and management. The case deviates from the expected pattern based on the Weigert-Meyer rule, emphasizing the importance of considering unique presentations in ureteral duplication cases.